ANALISIS KEISHIKIMEISHI TOKORO, KOTO DAN MONO DALAM KALIMAT BAHASA JEPANG - Hayudhitami, Rumbi; rosliana, lina; Ratna, Maharani (Program Studi Sastra Jepang, Fakultas Ilmu Budaya, Universitas Diponegoro, 2016)
The purpose of this research is to identify the structures and meanings ofkeishikimeishi tokoro, koto and mono. The author chose the title due to the lack ofexplanation of those words in Japanese textbooks, beside that keishikimeishitokoro,koto and mono have some similarities on meanings and structures.The method that been used in this research is a descriptive method. To write thisthesis, firstly, the author collected the data, analyzed the data and then presentedthe result. Keishikimeishi tokoro, koto and mono can be attached with adjective,noun and verb. Keishikimeishi tokoro, koto and mono in Indonesian language canbe interpresented as “something” or “case”. Although keishikimeishi tokoro, kotoand mono have the same meaning in Indonesian language, they actually havemore deeper meaning.